Experimental trace element partition coefficients for upper mantle pyroxenites coexisting with H2O with CO2, NaCl and NH3 fluids - Matthew J. M. Phillips; Svyatoslav S. Shcheka; Stephen F. Foley (Contributions to Mineralogy and Petrology, 2026)
Experimental determinations of trace element distribution between rocks/minerals and fluids at mantle pressures and temperatures have concentrated on eclogite and on fluids containing H 2 O with or without the addition of NaCl. Here we present data for websterite (pyroxenite) coexisting with five different fluids: H 2 O, H 2 O+CO 2 , H 2 O+NaCl, H 2 O+CO 2 +NaCl and H 2 O+NH 3 . All experiments were conducted at 1.5 GPa and 800˚C using glassy carbon fluid traps that were kept in a frozen state following experiments until trace elements in the fluid traps were analysed by laser cryoablation-ICP-MS. Results show that Rb, Ba, Sr, Pb and Li are fluid-mobile, with lower rock/fluid partition coefficients (D Rock/Fluid ) for all mixed fluids relative to pure H 2 O. Lowest values (0.0004–0.123) are found for H 2 O+NH 3 fluids. Almost all for the REE are 2 O+CO 2 +NaCl and H 2 O+NH 3 fluids, as are the HFSE, which also show lower D Rock/Fluid than for eclogites, with or without NaCl. Re and Pt are fluid-mobile, with D Re Pt and lowest values for both in H 2 O+CO 2 fluids. The first row transition elements show D-values ranging from 0.0004 to 2.88 with only 4 of 35 data points > 1. D Rock/Fluid increase in the order Cu Rock/Fluid ,particularly low-Al clinpyroxenes.

Skeletal structure and adaptive mechanisms of corals inhabiting a mangrove environment - Dayana Chadda-Harmer; Maria Byrne; Matthew Foley; Georgia Barrington-Smith; Emma F. Camp; Shawna A. Foo (Coral Reefs, 2026)
Coral skeletons form the foundational framework of coral reef ecosystems but are threatened by climate change stress. Under sub-optimal conditions, skeletal calcification rates decrease, and corals have been observed to form more porous skeletal structures, raising concerns of sublethal effects under future ocean conditions. Understanding how the structure of coral skeletons will be impacted by multiple, co-occurring climate change stressors and how different coral species will respond is of paramount importance to understand the future of coral reefs. Here, we examined the skeletal structure of corals living in a mangrove system. Mangrove environments possess sub-optimal seawater conditions and provide a natural setting to examine the long-term effects of environmental stressors on the skeletons of resident corals as well as identify mechanisms that corals may adopt to survive. Using micro-computed tomography, we investigated the effects of environmental conditions ranging from mangrove habitat to open reef on the skeletal structure of Pocillopora acuta , Acropora cf. millepora and Montipora cf. digitata , in the northern Great Barrier Reef. Corals were collected from sites with differing distance from the mangrove system at Low Isles. Species-specific structural changes were recorded in coral skeletons in response to distance from the mangroves. P. acuta had more porous and thinner skeletons closer to the mangroves, where seawater conditions were sub-optimal. Montipora cf. digitata was able to maintain a robust skeleton in the mangrove environment. This coral also possessed more dispersed but larger corallites at these sites, potentially availing of increased food availability in mangroves as a mechanism to support skeletal growth. This study suggests the integrity of coral skeletons will be compromised by climate change stress but that some coral species may be able to utilise mechanisms to maintain normal skeletal growth under sub-optimal conditions.

Navigating danger: Watercraft-related mortality of sea turtles in the United States Atlantic and Gulf coastal waters - Mariana M.P.B. Fuentes; Brian A. Stacy; Susan G. Barco; Robert A. DiGiovanni; Karen M. Dourdeville; Kimberly F. Durham; Mark Faherty; Sarah A. Finn; Allen M. Foley; Matthew H. Godfrey; Robert F. Hardy; Lyndsey N. Howell; et al. (Biological Conservation, 2025)

Evaluating the influence of high-resolution image capture on the signal strength of blue intensity and quantitative wood anatomy metrics from whitebark pine - Savannah A. Collins-Key; Maegen L. Rochner; Karen E. King; April L. Kaiser; Grant L. Harley; Zachary Foley; Matthew F. Bekker; Georg von Arx (Dendrochronologia, 2025)

Testing food web theory in a large lake: The role of body size in habitat coupling in Lake Michigan - Bryan M. Maitland; Harvey A. Bootsma; Charles R. Bronte; David B. Bunnell; Zachary S. Feiner; Kari H. Fenske; William W. Fetzer; Carolyn J. Foley; Brandon S. Gerig; Austin Happel; Tomas O. Höök; Friedrich W. Keppeler; et al. (Ecology, 2024)
The landscape theory of food web architecture (LTFWA) describes relationships among body size, trophic position, mobility, and energy channels that serve to couple heterogenous habitats, which in turn promotes long‐term system stability. However, empirical tests of the LTFWA are rare and support differs among terrestrial, freshwater, and marine systems. Further, it is unclear whether the theory applies in highly altered ecosystems dominated by introduced species such as the Laurentian Great Lakes. Here, we provide an empirical test of the LTFWA by relating body size, trophic position, and the coupling of different energy channels using stable isotope data from species throughout the Lake Michigan food web. We found that body size was positively related to trophic position, but for a given trophic position, organisms predominately supported by pelagic energy had smaller body sizes than organisms predominately supported by nearshore benthic energy. We also found a hump‐shaped trophic relationship in the food web where there is a gradual increase in the coupling of pelagic and nearshore energy channels with larger body sizes as well as higher trophic positions. This highlights the important role of body size and connectivity among habitats in structuring food webs. However, important deviations from expectations are suggestive of how species introductions and other anthropogenic impacts can affect food web structure in large lakes. First, native top predators appear to be flexible couplers that may provide food web resilience, whereas introduced top predators may confer less stability when they specialize on a single energy pathway. Second, some smaller bodied prey fish and invertebrates, in addition to mobile predators, coupled energy from pelagic and nearshore energy channels, which suggests that some prey species may also be important integrators of energy pathways in the system. We conclude that patterns predicted by the LTFWA are present in the face of species introductions and other anthropogenic stressors to a degree, but time‐series evaluations are needed to fully understand the mechanisms that promote stability.

Indole-3-acetic acid promotes growth in bloom-forming Microcystis via an antioxidant response - Hunter R. Baylous; Matthew F. Gladfelter; Malia I. Gardner; Madalynn Foley; Alan E. Wilson; Morgan M. Steffen (Harmful Algae, 2024)

Comparing travel behaviour characteristics and correlates between large and small Kenyan cities (Nairobi versus Kisumu) - Lambed Tatah; Louise Foley; Tolu Oni; Matthew Pearce; Charles Lwanga; Vincent Were; Felix Assah; Yves Wasnyo; Ebele Mogo; Gabriel Okello; Stephen Mogere; Charles Obonyo; et al. (Journal of Transport Geography, 2023)

Geographic and taxonomic variation in adaptive capacity among mountain-dwelling small mammals: Implications for conservation status and actions - Erik A. Beever; Jennifer L. Wilkening; Peter D. Billman; Lindsey L. Thurman; Kristina A. Ernest; David H. Wright; Alisha M. Gill; April C. Craighead; Nolan A. Helmstetter; Leona K. Svancara; Meghan J. Camp; Sabuj Bhattacharyya; et al. (Biological Conservation, 2023)

Application of Ge/Si ratios to ultramafic alkaline rocks using a novel LA-ICP- MS/MS method - Matthew J.M. Phillips; Stephen F. Foley; Olivier Alard (Chemical Geology, 2023)

Testing a global standard for quantifying species recovery and assessing conservation impact - Molly K. Grace; H. Resit Akçakaya; Elizabeth L. Bennett; Thomas M. Brooks; Anna Heath; Simon Hedges; Craig Hilton‐Taylor; Michael Hoffmann; Axel Hochkirch; Richard Jenkins; David A. Keith; Barney Long; et al. (Conservation Biology, 2021)
Recognizing the imperative to evaluate species recovery and conservation impact, in 2012 the International Union for Conservation of Nature (IUCN) called for development of a “Green List of Species” (now the IUCN Green Status of Species). A draft Green Status framework for assessing species’ progress toward recovery, published in 2018, proposed 2 separate but interlinked components: a standardized method (i.e., measurement against benchmarks of species’ viability, functionality, and preimpact distribution) to determine current species recovery status (herein species recovery score ) and application of that method to estimate past and potential future impacts of conservation based on 4 metrics ( conservation legacy, conservation dependence , conservation gain , and recovery potential ). We tested the framework with 181 species representing diverse taxa, life histories, biomes, and IUCN Red List categories (extinction risk). Based on the observed distribution of species’ recovery scores, we propose the following species recovery categories : fully recovered, slightly depleted, moderately depleted, largely depleted, critically depleted, extinct in the wild, and indeterminate. Fifty‐nine percent of tested species were considered largely or critically depleted. Although there was a negative relationship between extinction risk and species recovery score, variation was considerable. Some species in lower risk categories were assessed as farther from recovery than those at higher risk. This emphasizes that species recovery is conceptually different from extinction risk and reinforces the utility of the IUCN Green Status of Species to more fully understand species conservation status. Although extinction risk did not predict conservation legacy, conservation dependence, or conservation gain, it was positively correlated with recovery potential. Only 1.7% of tested species were categorized as zero across all 4 of these conservation impact metrics , indicating that conservation has, or will, play a role in improving or maintaining species status for the vast majority of these species. Based on our results, we devised an updated assessment framework that introduces the option of using a dynamic baseline to assess future impacts of conservation over the short term to avoid misleading results which were generated in a small number of cases, and redefines short term as 10 years to better align with conservation planning. These changes are reflected in the IUCN Green Status of Species Standard.

Ecological regime shift drives declining growth rates of sea turtles throughout the West Atlantic - Karen A. Bjorndal; Alan B. Bolten; Milani Chaloupka; Vincent S. Saba; Cláudio Bellini; Maria A. G. Marcovaldi; Armando J. B. Santos; Luis Felipe Wurdig Bortolon; Anne B. Meylan; Peter A. Meylan; Jennifer Gray; Robert Hardy; et al. (Global Change Biology, 2017)
Somatic growth is an integrated, individual‐based response to environmental conditions, especially in ectotherms. Growth dynamics of large, mobile animals are particularly useful as bio‐indicators of environmental change at regional scales. We assembled growth rate data from throughout the West Atlantic for green turtles, Chelonia mydas , which are long‐lived, highly migratory, primarily herbivorous mega‐consumers that may migrate over hundreds to thousands of kilometers. Our dataset, the largest ever compiled for sea turtles, has 9690 growth increments from 30 sites from Bermuda to Uruguay from 1973 to 2015. Using generalized additive mixed models, we evaluated covariates that could affect growth rates; body size, diet, and year have significant effects on growth. Growth increases in early years until 1999, then declines by 26% to 2015. The temporal (year) effect is of particular interest because two carnivorous species of sea turtles—hawksbills, Eretmochelys imbricata, and loggerheads, Caretta caretta —exhibited similar significant declines in growth rates starting in 1997 in the West Atlantic, based on previous studies. These synchronous declines in productivity among three sea turtle species across a trophic spectrum provide strong evidence that an ecological regime shift ( ERS ) in the Atlantic is driving growth dynamics. The ERS resulted from a synergy of the 1997/1998 El Niño Southern Oscillation ( ENSO )—the strongest on record—combined with an unprecedented warming rate over the last two to three decades. Further support is provided by the strong correlations between annualized mean growth rates of green turtles and both sea surface temperatures ( SST ) in the West Atlantic for years of declining growth rates ( r = −.94) and the Multivariate ENSO Index ( MEI ) for all years ( r = .74). Granger‐causality analysis also supports the latter finding. We discuss multiple stressors that could reinforce and prolong the effect of the ERS . This study demonstrates the importance of region‐wide collaborations.

Rapid water quality change in the E lwha R iver estuary complex during dam removal - Melissa M. Foley; Jeffrey J. Duda; Matthew M. Beirne; Rebecca Paradis; Andrew Ritchie; Jonathan A. Warrick (Limnology and Oceanography, 2015)
Dam removal in the United States is increasing as a result of structural concerns, sedimentation of reservoirs, and declining riverine ecosystem conditions. The removal of the 32 m Elwha and 64 m Glines Canyon dams from the Elwha River in Washington, U.S.A., was the largest dam removal project in North American history. During the 3 yr of dam removal—from September 2011 to August 2014—more than ten million cubic meters of sediment was eroded from the former reservoirs, transported downstream, and deposited throughout the lower river, river delta, and nearshore waters of the Strait of Juan de Fuca. Water quality data collected in the estuary complex at the mouth of the Elwha River document how conditions in the estuary changed as a result of sediment deposition over the 3 yr the dams were removed. Rapid and large‐scale changes in estuary conditions—including salinity, depth, and turbidity—occurred 1 yr into the dam removal process. Tidal propagation into the estuary ceased following a large sediment deposition event that began in October 2013, resulting in decreased salinity, and increased depth and turbidity in the estuary complex. These changes have persisted in the system through dam removal, significantly altering the structure and functioning of the Elwha River estuary ecosystem.

NanoXCT: A Novel Technique to Probe the Internal Architecture of Pharmaceutical Particles - Jennifer Wong; Dexter D’Sa; Matthew Foley; John Gar Yan Chan; Hak-Kim Chan (Pharmaceutical Research, 2014)

10Be, 18O and radiogenic isotopic constraints on the origin of adakitic signatures: a case study from Solander and Little Solander Islands, New Zealand - Fiona V. Foley; Simon Turner; Tracy Rushmer; John T. Caulfield; Nathan R. Daczko; Paul Bierman; Matthew Robertson; Craig D. Barrie; Adrian J. Boyce (Contributions to Mineralogy and Petrology, 2014)

Foliage Chemistry Influences Tree Choice and Landscape Use of a Gliding Marsupial Folivore - Kara N. Youngentob; Ian R. Wallis; David B. Lindenmayer; Jeff T. Wood; Matthew L. Pope; William J. Foley (Journal of Chemical Ecology, 2011)